Molecular Plant Breeding - Beavis, William (Open textbook library.)
This book focuses on genomics and plant biotechnology approaches used in plant breeding, the analysis of genomic data, and their application in quality control measures. The application of alternative genomic technologies to enhance conventional breeding strategies is also presented.